The Influence Of School Leadership And School Management On Student Learning Motivation - Wahyuna, Sri; Kristiawan, Muhammad; Martha, Alfroki (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to identify and describe: 1). influence principal's leadership on student learning motivation; 2) Effect of School Management on Student Motivation; 3) Effect of Principal Leadership and School Management on Student Motivation at SD Negeri Gugus 2, Semidang Aji District. This research uses descriptive quantitative method. The population in this study were 64 teachers. The data collection techniques used were questionnaires and documentation. Data were analyzed using simple linear and multiple linear regression formulas. The results showed that: 1) there was a significant influence of the principal's leadership on student learning motivation; 2) there is a significant effect of school management on student learning motivation; 3) there is a significant influence of the principal's leadership and school management on student learning motivation at SD Negeri Gugus 2, Semidang Aji District. The magnitude of the influence of the principal's leadership and school management on student learning motivation at SD Negeri Gugus 2, Semidang Aji District is 48.4%, the remaining 51.6% is influenced by other factors that are not included in the variable variables in this study.